Phylogenetic conservatism drives nutrient dynamics of coral reef fishes - Allgeier, Jacob E.; Weeks, Brian C.; Munsterman, Katrina S.; Wale, Nina; Wenger, Seth J.; Parravicini, Valeriano; Schiettekatte, Nina M. D.; Villéger, Sébastien; Burkepile, Deron E. (Nature communications, 2021)
The relative importance of evolutionary history and ecology for traits that drive ecosystem processes is poorly understood. Consumers are essential drivers of nutrient cycling on coral reefs, and thus ecosystem productivity. We use nine consumer “chemical traits” associated with nutrient cycling, collected from 1,572 individual coral reef fishes (178 species spanning 41 families) in two biogeographic regions, the Caribbean and Polynesia, to quantify the relative importance of phylogenetic history and ecological context as drivers of chemical trait variation on coral reefs. We find: ( 1 ) phylogenetic relatedness is the best predictor of all chemical traits, substantially outweighing the importance of ecological factors thought to be key drivers of these traits, ( 2 ) phylogenetic conservatism in chemical traits is greater in the Caribbean than Polynesia, where our data suggests that ecological forces have a greater influence on chemical trait variation, and ( 3 ) differences in chemical traits between regions can be explained by differences in nutrient limitation associated with the geologic context of our study locations. Our study provides multiple lines of evidence that phylogeny is a critical determinant of contemporary nutrient dynamics on coral reefs. More broadly our findings highlight the utility of evolutionary history to improve prediction in ecosystem ecology. The relative importance of evolutionary history and ecology for traits that drive ecosystem processes is poorly understood. Analyzing nine traits associated with fish stoichiometry from 1,572 individuals yields multiple lines of evidence that phylogeny is a critical determinant of nutrient cycling in coral reefs.